Performance-based budgeting in public sector and managerial performance with leadership as moderating variable / Indrawati Yuhertiana and Fatun Fatun - Yuhertiana, Indrawati; Fatun, Fatun (Universiti Teknologi MARA Cawangan Sarawak, 2020)
This is a research of managerial performance in public sector. This research has two objectives, first, to test the effect of performance-based budgeting on the performance of government officials. Second, examine the role of leadership style in moderating the effect of performance-based budgeting on the performance of government officials. This research uses a quantitative approach. The questionnaires were distributed to local government officials in Pamekasan regency, Indonesia. The sampled 131 respondents were civil servants working in local government work units. The analysis technique uses Partial Least Square. Hypothesis test results found that performance-based budgeting affects the managerial performance of government officials. However, leadership has not proven to play a role as a variable that is able to moderate the effect of performance-based budgeting on the performance of government officials.